Comprehension of HIV/AIDS messages in Lesotho - Olutunmise Adesola Ojo; Rudi de Lange (Communicare)
Targeted audiences do not always comprehend HIV/AIDS visual campaigns that are meant to educate and inform, and thus such campaigns do not result in a positive change in behaviour and attitude. This is possibly ascribable to the inappropriate use of graphic imagery and other visual elements in many such campaigns. Even though the cost of the ineffective use of graphic images in information and awareness might be difficult to calculate – especially with regard to health-related problems in which lives are involved, – the effectiveness of any visual healthcommunication material in terms of meaningful learning, comprehension or retention can nevertheless be determined by means of post-testing. In this study, the comprehension of the loveLife outdoor campaign material was thus post-tested amongst 301 subjects from five high schools in both urban and rural areas. The study set out to determine the subjects’ comprehension of both the messages and the graphic imagery and evaluated the material for self-efficacy. The results indicate that suitable graphic imagery fosters message comprehension, that inappropriate imagery inhibits comprehension, and that realistic and appropriate imagery is preferred to abstract and representational imagery. In addition, it was found that familiar images are a vehicle towards improved comprehension of HIV/AIDS messages.